2016
DOI: 10.3389/fphar.2016.00226
|View full text |Cite|
|
Sign up to set email alerts
|

Ophthalmic Combination of SurR9-C84A and Trichostatin-A Targeting Molecular Pathogenesis of Alkali Burn

Abstract: Background: Alkali burn is a frequently occurring ocular injury that resembles ocular inflammation caused by eye allergies, infection, and refractive surgeries.Methods: We investigated the synergistic regenerative potential of dominant negative survivin mutant (SurR9-C84A) and histone deacetylase (HDAC) inhibitor trichostatin-A (TSA) against alkali burn and corneal haze using human keratocytes and rabbit alkali burn model (Female New Zealand white rabbits).Results: Combination of SurR9-C84A and TSA suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the present study, large vacuoles were found in the corneal stroma in eyes post-NaOH insult. In our previous study, we found that combination treatment of dominant negative survivin mutant (SurR9-C84A) and histone deacetylase inhibitor trichostatin-A (TSA) is effective for maintaining the corneal tissue’s integrity in rabbit alkaline burn model ( Roy et al, 2016 ). Moreover, including additional biomarkers of the disease pathway in the proposed rat model, will give a better understanding of haze/scarring mechanisms and will provide more information on the effectiveness of the treatment for future work in human trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, large vacuoles were found in the corneal stroma in eyes post-NaOH insult. In our previous study, we found that combination treatment of dominant negative survivin mutant (SurR9-C84A) and histone deacetylase inhibitor trichostatin-A (TSA) is effective for maintaining the corneal tissue’s integrity in rabbit alkaline burn model ( Roy et al, 2016 ). Moreover, including additional biomarkers of the disease pathway in the proposed rat model, will give a better understanding of haze/scarring mechanisms and will provide more information on the effectiveness of the treatment for future work in human trials.…”
Section: Discussionmentioning
confidence: 99%
“…These nanoparticles are not separable by centrifuging hence, in order to remove the unreacted STPP and unencapsulated proteins they were dialyzed using a 100 kDa dialysis tubing. The suspension was then added to 30 mg of EDC and 15 mg of NHS and stirred for 30 min ( Roy et al, 2016 ). The alpha-SMA antibody suspension (100 μg/mL in 3 mL of PBS) was added dropwise at room temperature (25 ± 5°C) under sustained magnetic stirring for 12 h. The solution was dialyzed using a 100 kDa dialysis tubing to remove unreacted antibody and EDC or NHS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation